An anthropometric study of intercondylar femur notch with MRI analysis - Patidar, Aditya; Arora, Harshul; Sharma, Jay Kumar; Jain, Sarvagya (International Journal of Research in Orthopaedics, 2023)
Background: Anterior cruciate ligament is the most common ligament injury of knee. The bony anatomy of femur and tibia is responsible for normal knee kinematics and static stability. Intercondylar notch dimensions is considered as a significant predictive risk factor for ACL tear. Narrow femoral intercondylar notch width in either sex were major correlating factors. Aim was to evaluate the intercondylar femur notch dimensions in patients of knee injury using magnetic resonance imaging at RD Gardi Medical College, Ujjain, Madhya Pradesh. Methods: This is a prospective study consist of 400 patients carried out from October 2020 to August 2022 in the Department of Orthopaedics, RDGMC Ujjain. All the patients of knee injury including ACL tear and age 18 years to 60 years are included in the study. Patient less than 18 years and more than 60 years were excluded from the study. Dicom radiant software is used as statistical tool to analyse the data. Various intercondylar notch dimensions in different sections are measured using MRI in the dicom software. Results: The cut off values of axial NWI, NSI, NDI as 0.238, 0.662, 0.472 respectively. Conclusions: We conclude that narrow femoral intercondylar notch, lower notch width index increases the risk of an ACL tear in the given population. This would help in identification of people at risk for ACL injuries. Our study provides a comprehensive analysis on the risk factor of ACL tear, which would help in betterment of the patients at danger for anterior cruciate ligament injury. People with decreased notch dimensions should be educated on the high risk of ACL tear and be given proper prophylactic precautions.